2020
DOI: 10.1371/journal.ppat.1008844
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus evades ZAP detection by suppressing CpG dinucleotides in the major immediate early 1 gene

Abstract: The genomes of RNA and small DNA viruses of vertebrates display significant suppression of CpG dinucleotide frequencies. Artificially increasing dinucleotide frequencies results in substantial attenuation of virus replication, suggesting that these compositional changes may facilitate recognition of non-self RNA sequences. Recently, the interferon inducible protein ZAP, was identified as the host factor responsible for sensing CpG in viral RNA, through direct binding and possibly downstream targeting for degra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(77 citation statements)
references
References 66 publications
(128 reference statements)
6
70
1
Order By: Relevance
“…Consistently, scanning analysis demonstrates that the IE1 gene is the only region of the HCMV genome that is suppressed for CpG content [ 76 ]. In accordance, Lin et al demonstrated that HCMV transcripts with high CpG content are specifically targeted by ZAP, while the CpG-suppressed IE1 transcript remains unaffected [ 75 ]. However, artificially increasing the IE1 CpG content by introducing mutations into the IE1 coding region renders IE1 accessible to ZAP inhibition.…”
Section: Hcmv Evades Zap Detection By Suppressing Cpg Dinucleotidmentioning
confidence: 65%
See 1 more Smart Citation
“…Consistently, scanning analysis demonstrates that the IE1 gene is the only region of the HCMV genome that is suppressed for CpG content [ 76 ]. In accordance, Lin et al demonstrated that HCMV transcripts with high CpG content are specifically targeted by ZAP, while the CpG-suppressed IE1 transcript remains unaffected [ 75 ]. However, artificially increasing the IE1 CpG content by introducing mutations into the IE1 coding region renders IE1 accessible to ZAP inhibition.…”
Section: Hcmv Evades Zap Detection By Suppressing Cpg Dinucleotidmentioning
confidence: 65%
“…A recent arrayed ISG expression screening performed by Lin and colleagues identified ZAP to restrict HCMV in a manner that is independent of IRF3. Overexpression and knockdown experiments displayed decreased or increased virus replication, respectively, further confirming ZAP as a RF against HCMV [ 75 ]. For herpesviruses, the pattern of CpG dinucleotide frequencies is distinct: while the majority of alpha-herpesviruses demonstrate little or no CpG suppression, gamma-herpesviruses exhibit substantial suppression across the genome.…”
Section: Hcmv Evades Zap Detection By Suppressing Cpg Dinucleotidmentioning
confidence: 98%
“…ZAP preference for CG-rich substrates could explain in part why many RNA viruses infecting mammals and other vertebrates, such as IAV and SARS-CoV-2, exhibit CG suppression (152)(153)(154)(155). ZAP can even sense CG dinucleotides within individual RNA transcripts of DNA viruses, as in the case of human cytomegalovirus (156). Here, CG suppression within the major immediate early transcript 1 confers ZAP resistance (156).…”
Section: Zapmentioning
confidence: 99%
“…ZAP can even sense CG dinucleotides within individual RNA transcripts of DNA viruses, as in the case of human cytomegalovirus ( 156 ). Here, CG suppression within the major immediate early transcript 1 confers ZAP resistance ( 156 ). However, CG suppression does not always confer resistance to ZAP as in the case of SARS-CoV-2 ( 154 ).…”
Section: Multifaceted Rna-dependent Antiviral Mechanisms: From Targetmentioning
confidence: 99%
See 1 more Smart Citation